2020
DOI: 10.4103/ajns.ajns_121_20
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding complications in endoscopic trans-sphenoidal surgery for pituitary adenoma: A beginner's perspective

Abstract: Introduction: We aimed to analyze the difficulties and complications experienced while as a beginner in endoscopic transnasal transsphenoidal approach for pituitary adenomas. Materials and Methods: We retrospectively analyzed 83 cases done from June 2016 to August 2019. Navigation-guided endoscopic transnasal transsphenoidal approach was used in all the cases. Results: Gross total tumor removal was achieved in 55 (66.26%) patients. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This study is limited by its retrospective nature. Although this data set's prevalence of apoplexy and SPH are concordant with the existing literature, [5][6][7][8][20][21][22] the small number of cases makes assessment of long-term outcomes more challenging. Specifically, although there were no mortalities in our cohort, other recent studies have found that up to 42% of SPH cases may be fatal.…”
Section: Limitations and Generalizabilitysupporting
confidence: 80%
See 1 more Smart Citation
“…This study is limited by its retrospective nature. Although this data set's prevalence of apoplexy and SPH are concordant with the existing literature, [5][6][7][8][20][21][22] the small number of cases makes assessment of long-term outcomes more challenging. Specifically, although there were no mortalities in our cohort, other recent studies have found that up to 42% of SPH cases may be fatal.…”
Section: Limitations and Generalizabilitysupporting
confidence: 80%
“…[2][3][4] The rate of SPH after endonasal resection of pituitary neuroendocrine tumor ranges between 0.1% and 1.5, and composes 7.4% of 30-day readmissions for PitNET surgery. [5][6][7][8][9][10][11] Although this is similar to the rate in the broader neurosurgical population, 12 the specific risk factors for developing SPH after pituitary surgery are unknown and potentially unique. This topic has not been investigated thoroughly because of the low incidence of SPH, 13 and as a result, recommendations for prevention and surveillance are lacking.…”
mentioning
confidence: 75%
“…Of these three elements, only the arachnoid is found in every human (23). In the literature, CSF leaks have been reported varying from 0.5% to 10.3% (20). We had a total of 3 (13,6%) cases with postoperative CSF leak.…”
Section: Discussionmentioning
confidence: 94%
“…Pituitary adenomas are tumors of extraarachnoidal origin, so usually grow outside the confines of CSF (20). As the tumor lies in close relationship to the diaphragm sellae and subarachnoid space, there is always a risk of iatrogenic arachnoid breach (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation